PENENTUAN HARGA POKOK PRODUKSI PERUSAHAAN INDUSTRI - SAFRI SAFRI (JURNAL TEKNIK INDUSTRI, 2021)
Accounting industry recognizes two methods of determining the cost of production, these methods are cost method and process order cost method. In the order cost method, all costs incurred from the purchase of raw materials to the finished product, will be charged to the product ordered. As for the cost method process, the charging is only done based on the cost that actually occur until the product is completed. For the unique nature of the product, in the sense not want to be known by those who want to know the formula the company's products, accounting industry, must be engineered, reverse to hide the production process up to the finished product. Model Sell Buy on Industrial companies can be used for this purpose, because the results of the calculation are converted to the financial statements presents the same face to the Method of Cost Process.Keywords: Methods cost of the process, the order cost method, a model of buying and selling